Mode set focused hybrid estimation - Rienmüller, Theresa; Hofbaur, Michael; Travé-Massuy?s, Louise; Bayoudh, Mehdi (Zielona Góra: Uniwersytet Zielonogórski)
Estimating the state of a hybrid system means accounting for the mode of operation or failure and the current state of the continuously valued entities concurrently. Existing hybrid estimation schemes try to overcome the problem of an exponentially growing number of possible mode-sequence/continuous-state combinations by merging hypotheses and/or deducing likelihood measures to identify tractable sets of the most likely hypotheses.
Keywords: hybrid systems; fault detection and diagnosis; monitoring and estimation